Effect of Physalis peruviana (goldenberry) on postprandial glycemia in young adults - Rodríguez Ulloa, Sheila Lizett (Vallejian Medical Journal, 2007)
Physalis peruviana is a native plant from peruvian andes with many medicinal properties one of them is its antidiabetic effect. The objective of the study was to determine the effect of Physalis peruviana on postprandial 2 glycemia in young adults. Twenty six volunteers participated (age 25.03 ± 2.74 years, BMI 22.76 ± 1.48 kg/m ), being distributed randomly in two groups: group I consumed 25 g of fruit of Physalis peruviana and 40 minutes later received the glucose challenge, while the group II only received the last one. A blood sample was recollected at 30, 60, 90 and 120 minutes later in both groups. After three days, treatments were interchanged. We found in the control group an average basal glycemia of 89.2 ± 7.75 mg/dl, at 30 minutes postprandial 130.6 ± 14.92 mg/dl, at 60 minutes 116.2 ± 16.57 mg/dl, at 90 minutes 106.3 ± 13.65 mg/dl and at 120 minutes 93.1 ± 10.55 mg/dl. While in the problem group obtained glycemias of 85.9 ± 10.99 mg/dl, 123.6 ± 13.65 mg/dl, 109.1 ± 13.69 mg/dl, 96.8 ± 12.12 mg/dl and 86.3 ± 13.22 mg/dl respectively. At 90 minutes postprandial had a very significant difference (p < 0.01) and at 120 minutes a significant difference (p < 0.05) between values of glycemia in both groups. This allows us to conclude that Physalis peruviana decreases the glycemia at 90 and 120 minutes postprandial in young adults.